From theory to practice of designing for diversity: Applying intersectionality to improve HIV testing uptake - Elham Ghasemi; Fatemeh Rajabi; Reza Majdzadeh (PLoS ONE, 2025)
Introduction Given the critical perspective of intersectionality and its potential to identify the causes of inequalities, it has been employed increasingly in studies related to health. Despite the rich theoretical evidence about intersectionality, there is a need to consider this approach empirically. This study aimed to apply the intersectionality in practice for health policy makers and researchers seeking to reduce health inequalities. In this regard, we described the development of an intersectionality-based and context-specific intervention focusing on HIV testing uptake among Afghan immigrants in Iran. Methods This is an intervention development study. The intersectionality was used to design a peer-led intervention guided by the 2008 MRC framework. We undertook the following activities related to the three stages of the MRC framework: 1. Identifying the existing evidence (conducting a scoping review to investigate the application of intersectionality in designing and implementing health interventions; designing the checklist of applying the intersectionality in health interventions and programs); 2. Identifying and developing a program theory (conducting a realist review to identify why, how, and under what conditions peer interventions can improve HIV testing uptake among immigrants); and 3. Modeling process and outcomes (adapting the contextual factors identified by conducting a qualitative study and the realist review; extracting considerations regarding intersectionality principles using the checklist of applying the intersectionality in health interventions and programs; determining context specific, intersectionality-based and evidence-based intervention components for each of the intervention pathways). Results According to considerations regarding checklist of application of intersectionality principles, the intervention at the different individual, organizational, and policy levels with multiple strategies should be designed to respond to needs/conditions affecting HIV testing uptake among immigrants. We determined the peer-led intervention features to improve the use of HIV testing services in Afghan immigrants following the intersectionality principles, target group needs, and contextual conditions aiming to modify power structures. Intervention strategies included HIV information provision, support, community-based services, and structural interventions. Conclusion This study provides a practical framework for health planners and researchers seeking to reduce inequalities by presenting how intersectionality can influence the design of a health intervention. Accordingly, it is necessary to revisit the social relationships and power structures, determine the intervention components based on evidence tailored to the target group’s needs, and apply changes at different levels.